Comparative effectiveness of intergenerational service-learning programs on student outcomes of knowledge, attitude, and ageism. Issue 12 (2nd December 2021) - Bartlett, Sara P.; Solomon, Phyllis; Gellis, Zvi
ABSTRACT: Intergenerational service-learning for undergraduate students seeks to generate interest about the older adult population, while increasing knowledge and improving attitudes about aging and reducing ageism. It is difficult to make an impact on students' views in a short time period, such as an academic quarter. This comparative effectiveness study evaluated the efficacy of a 10-week intergenerational service-learning program administered to Psychology of Aging undergraduates to determine if it increased knowledge about aging, improved attitudes about older adults, and reduced ageism more than a predominately didactic course with less service activity. A quasi-experimental design using a convenience sample compared pre- and posttest scores between the experimental intervention (n = 68) and comparison (n = 71) condition on The Facts on Aging Quiz Multiple Choice version, Aging Semantic Differential, and Fabroni Scale on Ageism. The experimental intervention, the Lives Well Lived program, matched students and older adults who met criteria for "successful aging, " in a mutual interviewing, life review project utilizing documentary film, photography, and creation of memoirs. Results determined that students in the experimental intervention showed less stereotypical beliefs and net bias about aging. Programs that are more relational, in-depth, more experiential and less didactic may be useful for consideration in undergraduate psychology or human service programs in reducing ageism and potential for increasing interest in careers in the field of aging.